2012
DOI: 10.1044/1058-0360(2012/11-0109)
|View full text |Cite
|
Sign up to set email alerts
|

The Time-Course of Lexical Activation During Sentence Comprehension in People With Aphasia

Abstract: Purpose To investigate the time-course of processing of lexical items in auditorily presented canonical (subject–verb–object) constructions in young, neurologically unimpaired control participants and participants with left-hemisphere damage and agrammatic aphasia. Method A cross modal picture priming (CMPP) paradigm was used to test 114 control participants and 8 participants with agrammatic aphasia for priming of a lexical item (direct object noun) immediately after it is initially encountered in the ongoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 39 publications
6
41
2
Order By: Relevance
“…The fact that people with aphasia had longer overall reading times than the controls is broadly consistent with the claim that slowed lexical access interferes with sentence processing (e.g., Ferril et al, 2012; Love et al, 2008; Swinney et al, 1996). However, even if the effects of verb mismatch were spurious, the people with aphasia showed significant effects of mismatch at the same point in the sentence as non-brain-damaged controls.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The fact that people with aphasia had longer overall reading times than the controls is broadly consistent with the claim that slowed lexical access interferes with sentence processing (e.g., Ferril et al, 2012; Love et al, 2008; Swinney et al, 1996). However, even if the effects of verb mismatch were spurious, the people with aphasia showed significant effects of mismatch at the same point in the sentence as non-brain-damaged controls.…”
Section: Discussionsupporting
confidence: 80%
“…This would be consistent with Love and colleagues’ claim that sentence comprehension deficits reflect slowed lexical processing, on the assumption that slowed lexical access should affect the time course with which lexical biases are activated (e.g., Ferril, Love, Walenski, & Shapiro, 2012; Love, Swinney, Walenski, & Zurif, 2008)…”
Section: Introductionsupporting
confidence: 88%
“…On average, participants with aphasia required twice as long as participants without aphasia to perform the experimental trials regardless of sentence stimulus condition. This finding is consistent with that of other researchers (e.g., Ferrill, Love, Walenski, & Shapiro, 2012) who have suggested that people with aphasia have slow processing speeds and highlights the need to allow ample processing time when interacting with people with aphasia.…”
Section: Processing Timesupporting
confidence: 92%
“…Downloaded by [Northwestern University] at 09:52 25 March 2015 Furthermore, the decrease in RT reported for the post-pronoun region in contexts where the depicted antecedent of the overt pronoun was the syntactic object along with the aphasic group's offline low-matching rates for the overt pronoun-object coindexation condition implies first of all that the aphasic processor gained momentarily access to the lexical bias of the overt pronoun in an implicit, at least not strategic fashion. The emergence of such effect on a late temporal window goes in line with former findings on lexical processing in Broca's aphasia showing a deficit in the timely activation of lexical form representations (Choy & Thompson, 2010;Ferrill, Love, Walenski, & Shapiro, 2012). The fact that such lexical bias did not impact matching decisions shows specifically impaired online integration of top-down discourse cues, despite comparatively spared bottom-up lexical integration.…”
Section: Downloaded By [Northwestern University] At 09:52 25 March 2015supporting
confidence: 69%